PENINGKATAN KINERJA SDM MELALUI KONDISI KERJA, KONTEN PEKERJAAN DAN PENGEMBANGAN KARIR DENGAN MEDIASI MOTIVASI KERJA - Muhamadun Muhamadun; Ghoniyah Nunung (Jurnal Bisnis dan Ekonomi, 2012)
Human resource is one of the most important assets of an organization. In other words, the success of an organization greatlydepends on the performance of its employees. Therefore, managers and experts endeavour to determine the most striking whatfactors most influence employee motivation. This study aimed to analyze the influence of Working Conditions,Work Content,Career Growth,on Work Motivationand Employee Performance of IAIN Walisongo. The participants of the study were selectedusing Proporsionate Stratified Random Samplingmethodto the staff of IAIN Walisongo. A sample of 137 employees working indifferent units andfakulty were randomly selected. The population of the study was geographically limited to employees ofIAIN Walisongo Semarang. The results showed that R2 value (coefficient of determination) of 0,396 means there is variation ofIAIN Walisongo employee performance. It can be explained that the influence of working conditions, work content, and careergrowth is 39,6%, while the rest of it, 60,4% is explained by other factors which are not examined. The significance of <alpha= 5%, indicated that the regression model can be used, there is influence of positive significance working conditions, workcontent, career growth and work motivation on performance HR together.Conclusion This study supports earlier theories thatalready exist and also presents managerial implications that can be used as a reference for improvement.Key words: working conditions, work content, career growth, work motivation and hr performace